Gender differences in cardiovascular risk, treatment, and outcomes: a post hoc analysis from the REWIND trial. (31st December 2023) - Ferrannini, Giulia; Maldonado, Juan M.; Raha, Sohini; Rao-Melacini, Purnima; Khatun, Rutaba; Atisso, Charles; Shurzinske, Linda; Gerstein, Hertzel C.; Rydén, Lars; Bethel, M. Angelyn
Abstract: Objectives . To assess whether the use of cardioprotective therapies for type 2 diabetes varies by gender and whether the risk of cardiovascular events is higher in women versus men in the REWIND trial, including an international type 2 diabetes patient population with a wide range of baseline risk. Design . Gender differences in baseline characteristics, cardioprotective therapy, and the achieved clinical targets at baseline and two years were analyzed. Hazards for cardiovascular outcomes (fatal/nonfatal stroke, fatal/nonfatal myocardial infarction, cardiovascular death, all-cause mortality, and heart failure hospitalization), in women versus men were analyzed using two Cox proportional hazard models, adjusted for randomized treatment and key baseline characteristics respectively. Time-to-event analyses were performed in subgroups with or without history of cardiovascular disease using Cox proportional hazards models that included gender, subgroup, randomized treatment, and gender-by-subgroup interactions. Results . Of 9901 participants, 46.3% were women. Significantly fewer women than men had a cardiovascular disease history. Although most women met treatment targets for blood pressure (96.7%) and lipids (72.8%), fewer women than men met the target for cardioprotective therapies at baseline and after two years, particularly those with prior cardiovascular disease, who used less renin-angiotensin-aldosterone system inhibitors, statins, and aspirin than men. Despite these differences, women had lower hazards than men for all outcomes except stroke. No significant gender and cardiovascular disease history interactions were identified for cardiovascular outcomes. Conclusions . In REWIND, most women met clinically relevant treatment targets, but in lower proportions than men. Women had a lower risk for all cardiovascular outcomes except stroke. Clinical trials.gov registration number: NCT01394952